Predictors of failure of DISE-directed adenotonsillectomy in children with sleep disordered breathing - Noura Alsufyani; Andre Isaac; Manisha Witmans; Paul Major; Hamdy El-Hakim (Journal of Otolaryngology - Head and Neck Surgery, 2017)
Abstract Background Adenotonsillectomy (AT) is the most commonly performed procedure for sleep disordered breathing (SDB) in pediatrics. However, 20-40% of patients will have persistent signs and symptoms of SDB after AT. Drug-induced sleep endoscopy (DISE) has the potential to individualize surgical treatments and avoid unnecessary or unsuccessful surgeries. The objective of this study was to determine the predictors of failure of DISE-directed adenoidectomy and/or tonsillectomy in otherwise healthy children with SDB. Methods We retrospectively reviewed a prospective database of children who presented with SDB. All patients underwent preoperative pulse oximetry (PO), followed by DISE with T ± A, The variables documented included demographics, ethnicity, co-morbidities, family history, McGill Oximetry Score (MOS) on PO, as well as findings of collapse and or obstruction on DISE and symptom resolution based on modified Pediatric Sleep Questionnaire (PSQ). The primary outcome was the independent predictors of treatment failure based on multivariate binary logistic regression. Results Three hundred eighty-two patients satisfied the inclusion criteria. Based on post-operative modified PSQ, SDB resolved in 259 patients (68%), whereas 123 (32%) had persistent symptoms. On bivariate analysis, neuropsychiatric diagnosis (r = 0.286, p = 0.042), history of sleepwalking or enuresis (r = 0.103, p = 0.044), MOS (r = 0.123, p = 0.033), presence of DNS (r = 0.107, p = 0.036), and presence of laryngomalacia (r = 0.122, p = 0.017) all positively correlated with treatment failure. Small tonsil size on DISE correlated with treatment failure (r = −0.180, p < 0.001). Multivariate analysis identified age greater than 7 years (OR = 1.799, [95% CI 1.040–3.139], p = 0.039), obesity (OR = 2.032, [95% CI 1.043–3.997], p = 0.040), chronic rhinitis (OR = 1.334, [95% CI 1.047–1.716], p = 0.025), deviated nasal septum (OR = 1.745, [95% CI 1.062–2.898], p = 0.031) and tonsil size (OR = 0.575, [95% CI 0.429–0.772], p < 0.01) as independent predictors of treatment failure. Conclusions Obese, asthmatic, and children older than seven years are at increased risk of treatment failure after DISE-directed AT. Several DISE findings can independently predict AT failure, including tonsil size, degree of chronic rhinitis, and the presence of a deviated nasal septum, and can be addressed at a second stage. Further research is needed into the role of DISE in surgically naïve patients with SDB, and to compare DISE-directed surgery with the current standard of care.